Phototherapy Radiometer with AS7262 Sensor - Ichwan Syahrul Bahtiar; Andjar Pudji; I Dewa Gede Hari Wisana (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
The phototherapy is a device used in hyperbilirubinemia therapy by using blue light radiation with ranges between 425nm-475nm. The effectiveness of hyperbilirubinemia therapy depends on the amount of energy emitted by light which expressed in μW/cm2. The purpose of this study is to develop a low-cost and high accuracy Phototherapy radiometer. Measurement of blue light irradiance using the AS7262 sensor which can measure the irradiance of visible light with a wavelength of 450nm, 500nm, 550nm, 570nm, 600nm, 650nm with relative responsiveness of 1 time at each wavelength. SD card memory is used to save measurement data of irradiance so that it can be processed later. Based on the blue light irradiance data collected the smallest error value is 0,40% at a distance of 10cm while the biggest error value is 9,01%  at a distance of 30cm. After testing the entire system, the device can be used according to its function and purpose.